The finance and growth of the Lancashire cotton textile industry, 1870-1914 - Toms, John Steven (1996)
Using accounting records and financial data, a business history of the Lancashire textile industry from 1870 to 1914 is presented. Issues of technology and industry structure, which have attracted a great deal of comment are first re-addressed. The discussion is then widened to include other aspects of the industry which have previously been neglected, namely the social processes of capital accumulation with reference to those evolving relationships between managers and shareholders which, in the context of broader economic change, helped forge the special characteristics of Lancashire capitalism.